2023
DOI: 10.1038/s41467-023-40450-3
|View full text |Cite
|
Sign up to set email alerts
|

A common neuronal ensemble in nucleus accumbens regulates pain-like behaviour and sleep

Haiyan Sun,
Zhilin Li,
Zhentong Qiu
et al.

Abstract: A comorbidity of chronic pain is sleep disturbance. Here, we identify a dual-functional ensemble that regulates both pain-like behaviour induced by chronic constrictive injury or complete Freund’s adjuvant, and sleep wakefulness, in the nucleus accumbens (NAc) in mice. Specifically, a select population of NAc neurons exhibits increased activity either upon nociceptive stimulation or during wakefulness. Experimental activation of the ensemble neurons exacerbates pain-like (nociceptive) responses and reduces NRE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 82 publications
(186 reference statements)
0
3
0
Order By: Relevance
“…These modes involve different modules of noradrenergic neurons operating independently in terms of circuit function within their respective efferent domains, with distinct populations of cells assuming specific responsibilities [ 52 ]. Furthermore, there is evidence suggesting that the same group of cells can assume different roles [ 53 ]. Therefore, noradrenergic neurons in different parts of the LC may have different functions in pain, and even noradrenergic neurons in the same region may have different effects.…”
Section: Discussionmentioning
confidence: 99%
“…These modes involve different modules of noradrenergic neurons operating independently in terms of circuit function within their respective efferent domains, with distinct populations of cells assuming specific responsibilities [ 52 ]. Furthermore, there is evidence suggesting that the same group of cells can assume different roles [ 53 ]. Therefore, noradrenergic neurons in different parts of the LC may have different functions in pain, and even noradrenergic neurons in the same region may have different effects.…”
Section: Discussionmentioning
confidence: 99%
“…Our ndings build upon this concept, demonstrating how speci c astrocytes within ensembles, but not the entire population, integrate inputs to shape goal-related representations within the NAc. Such encoding of discrete stimuli and their corresponding behavioral responses has been demonstrated in NAc neuronal ensembles [50][51][52][53][54][55][56][57][58] . While further research is necessary to unravel the mechanistic interplay between these neuronal and astrocytic ensembles, the versatility of the AstroLight tool has the potential to advance the eld in addressing these questions.…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of ventral tegmental area activity causes neuropathic pain hypersensitivity, and the projection to the preoptic area leads to sleep disturbance. 488 The dual functions of the NAc may provide a target for therapies against pain and sleep disturbance comorbidity. Despite the lack of mechanistic research on frequent arousals, an observational study indicated that the arousal infraslow can appear at the interval of 50 s during non-rapid eye movement sleep.…”
Section: Mechanisms Of Pain Comorbiditiesmentioning
confidence: 99%